2022
DOI: 10.1109/access.2022.3152152
|View full text |Cite
|
Sign up to set email alerts
|

BERTFOREX: Cascading Model for Forex Market Forecasting Using Fundamental and Technical Indicator Data Based on BERT

Abstract: Foreign exchange (Forex) rate forecasting is presently pursued by many researchers as it plays an important role in financial technology and business. The challenge of Forex research lies in its characteristics, fluctuation, non-linearity, and random walk phenomena. Several related studies generate forecasting signals using fundamental data (FD) and technical indicator data (TI) to support Forex. FD is an indicator of country economic conditions, while TI shows the price pattern-based signal. However, these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The ensemble model takes all the signals from the different strategies and uses majority voting logic to decide what to do next [12] .The problem with this system is its low accuracy, and it was tested only on the EUR/USD dataset. Pornwattanavichai and Maneeroj [13] proposed a cascading model for the FOREX market. They made forecasts using Fundamental Data and Technical indications based on BERT.…”
Section: Related Workmentioning
confidence: 99%
“…The ensemble model takes all the signals from the different strategies and uses majority voting logic to decide what to do next [12] .The problem with this system is its low accuracy, and it was tested only on the EUR/USD dataset. Pornwattanavichai and Maneeroj [13] proposed a cascading model for the FOREX market. They made forecasts using Fundamental Data and Technical indications based on BERT.…”
Section: Related Workmentioning
confidence: 99%
“…In recent research, transformerbased natural language processing methods have shown promising results in financial text data analysis. Particularly Google's BERT model [22], as a transformer-based pretrained model, made remarkable progress in natural language processing and was applied to sentiment analysis of financial texts in many studies (e.g., [23,24]). For instance, Hiew et al's study shows that a BERT-based sentiment analysis approach is superior to models such as FastText or a multichannel Convolutional Neural Network (CNN) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Algunos trabajos notables, de previsión de la evolución de los tipos de cambio se basan en técnicas de inteligencia artificial. Entre los enfoques más avanzados se encuentran el aprendizaje profundo por refuerzo [489], la memoria a largo plazo (LSTM) [490], el análisis de sentimiento a partir de contenido textual [491,492], el análisis wavelet [493], los algoritmos genéticos [494], las máquinas de vectores de soporte y otros enfoques [495]. En un intento por mejorar la precisión de estos algoritmos, los investigadores han propuesto técnicas para combinarlos y formar sistemas más robustos.…”
Section: Construcción Del Modelo De Clasificaciónunclassified